2016
DOI: 10.18632/oncotarget.12243
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose green tea intake reduces incidence of atrial fibrillation in a Chinese population

Abstract: The aim of the present study was to assessthe association between green tea intake and incidence of atrial fibrillation (AF) in a Chinese population. A total of 801 (mean age: 62 years; 56% male) subjects were enrolled: 401 AF patients and 400 controls. All subjects completed a questionnaire and the associations between their green tea drinking habits and incidence of AF were assessed using the odds ratio (OR) and binary logistic regression. After multivariate adjustment, green tea intake presented as a protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…In a multi-ethnic study involving 6,508 participants, Miller et al found a statistically significant lower incidence of cardiovascular events in ≥ 1 cup/day tea drinkers (adjusted hazard ratio, 0.71; 95% CI, 0.53, 0.95) ( 34 ). A similar inverse association was observed between tea consumption and CVD mortality ( 35 ), risk of coronary heart disease (CHD) ( 36 ), incident MI ( 37 ), and both paroxysmal AF and persistent AF ( 38 ). Several studies have suggested that there was no correlation between tea consumption and the risk of developing CVD or CHD ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 53%
“…In a multi-ethnic study involving 6,508 participants, Miller et al found a statistically significant lower incidence of cardiovascular events in ≥ 1 cup/day tea drinkers (adjusted hazard ratio, 0.71; 95% CI, 0.53, 0.95) ( 34 ). A similar inverse association was observed between tea consumption and CVD mortality ( 35 ), risk of coronary heart disease (CHD) ( 36 ), incident MI ( 37 ), and both paroxysmal AF and persistent AF ( 38 ). Several studies have suggested that there was no correlation between tea consumption and the risk of developing CVD or CHD ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 53%
“…Several observational studies appear to have focused on outcomes related to the mind [32][33][34] or heart [35][36][37][38]. Longitudinal research found that regular tea drinking (green, fermented, floral) amongst older Chinese adults was associated with fewer depressive symptoms [39].…”
Section: Observational Evidencementioning
confidence: 99%
“…Other prospective research using data from the Chinese Kadoorie Biobank found that daily tea consumption (black, oolong or green tea) reduced is chaemic heart disease risk, particularly in rural, healthy weight, non-diabetic adults [36]. Liu DC, et al (2016) again conducted research in a Chinese population and found that low-dose green tea ingestion, which accounted for the frequency, concentration, and duration of green tea intake, lowered a trial fibrillation incidence [37]. In the Greek Ikaria Island Study (a region with one of the highest global life expectancies), tea drinking was associated with a reduced risk of CVD [38].…”
Section: Observational Evidencementioning
confidence: 99%
“…They showed that low doses of green tea had a significant protective effect on the incidence of paroxysmal and persistent AF. 98 …”
Section: Plants and Their Ingredients With Antiarhythmic Propertiesmentioning
confidence: 99%